Development of polycaprolactone-akermanite nanobiocomposite scaffolds via 3D printing: Structural, mechanical, and biological evaluation for bone tissue regeneration - Rahmatollah Emadi; Pegah Dehghanpour; Yeganeh Salehi; Sayed Reza Mortazavi (Journal of Materials Research and Technology)
Bone tissue engineering (BTE) focuses on restoring damaged bone by integrating biological and mechanical properties. Three-dimensional (3D) printing facilitates the fabrication of bioscaffolds, with intricate architectures, where polymers like polycaprolactone (PCL) are widely utilized due to their favorable biocompatibility and processability. Incorporating bio-ceramics like akermanite (Ca2MgSi2O7, AKR) into polymer matrices enhances scaffold properties, including cell viability, osteogenesis, angiogenesis, and antibacterial effects. In this study, akermanite nanoparticles were synthesized via the sol-gel method and incorporated into 3D-printed PCL scaffolds at varying concentrations (0, 15, 30, and 60 wt%) using robocasting. Structural characterizations (SEM, FTIR, and XRD) confirmed successful integration of akermanite. The synthesized nanoparticles had an average size of 113 ± 0.12 nm, promoting better dispersion and interfacial bonding. Increased akermanite content led to improved porosity (59.81 %–72.17 %) and hydrophilicity (contact angle reduced from 102.31° to 65.71°). Mechanical testing showed notable improvements in compressive strength, yield strength, and Young's modulus, reaching 28.24 ± 0.37 MPa, 5.27 ± 0.91 MPa, and 54.44 ± 6.34 MPa at PCL-60 %AKR. Degradation in phosphate-buffered saline (PBS) over 28 days showed a 7.5-fold increase in weight loss for PCL-60 %AKR compared to pure PCL. Bioactivity assessment confirmed apatite formation in simulated body fluid, increasing with akermanite content. MTT assay verified non-cytotoxicity, while MG-63 cell adhesion and proliferation improved on composite scaffolds. This cellular response was attributed to the release of bioactive ions. Overall, the 3D-printed PCL-60 %AKR scaffold demonstrates excellent structural, mechanical, and biological properties for bone regeneration.